Estudio de factibilidad para la creación de una empresa de servicios en Seguridad y Salud Ocupacional en la ciudad de Latacunga - Oto Catota, Aide Soraida (2022)
The objective of this research work was to develop a feasibility study for the creation of an Occupational Health and Safety service company in Latacunga city, which is focused on providing service to micro, small and medium-sized companies, since after More than 2 years after the appearance of COVID-19, the rules changed on occupational health and safety field, where it was necessary to carry out bibliographic reviews, over study environment and its objectives. The applied methodology for this research was quantitative approach, supported by other methods such as deductive, analytical and statistical, through the use of research techniques and instruments such as the interview, survey and questionnaire, which were applied to 4 experts of the area with more than 5 years of experience on field and 247 local companies, 690 companies of general ranking, published by Superintendency of Companies, Securities and Insurance, were taken as population, with this research it was possible to obtain cross-sectional information that allowed to know business management at occupational health and safety field, as well as important factors around the market target, which gave way to technical development of legal, operational and financial feasibility analysis, obtaining as a result that the proposed project is feasible from the market, technical, legal, operational and economic point of view, based on installed capacity, the goal of 6% participation as market share is set. When analyzing the project financially, an IRR of 18.68%, a NPV of $7,802.77 and a cost benefit of $1.13 with an estimated payback period of 3 years 21 days were obtained, thus demonstrating that it is feasible to create a service company at occupational health and safety area in Latacunga city.